The Application of Turn-Taking Strategies on THE BOYZ Podcast Highlight Episode: Conversation Analysis Reflection - Syani Dwi Fitriana; Slamet Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
A conversation is not all about a social activity that involves two people or more who chatter on anything. It has been regulated in the basic principles of spoken language in linguistics. The approach to analyzing the rules of interactive spoken language is mainly attached to the scope of conversation analysis which is commonly known as turn-taking. This research presents the appliance of turn-taking strategies and the patterns of turn-in-talk on THE BOYZ podcast conducted by bilingual speakers, which refers to the theory from Sacks et al. (1974). Furthermore, this study aims to identify the implication of language alternation usage by bilingual speakers in the conversation using the bilingual communication theory proposed by Mahecha and Auer (1986). The data are collectively derived from the utterances of the interview session transcribed on the DIVE Studios Podcasts' YouTube channel. The results revealed the parties on the podcast are more likely to use adjacency pairs among the types of turn-taking strategies and self-selection distribution of turn-allocation in the entire conversation. A genuine intent by bilingual speakers to shift the language within the discussion is to create an apparent approval or agreement and validation.